Effect of acute ingestion of ß-hydroxybutyrate salts on the response to graded exercise in trained cyclists - Evans, M.; Patchett, E.; Nally, R.; Kearns, R.; Larney, M.; Egan, B. (European Journal of Sport Science, 2018)
Acute ingestion of ketone salts induces nutritional ketosis by elevating ß-hydroxybutyrate (ßHB), but few studies have examined the metabolic effects of ingestion prior to exercise. Nineteen trained cyclists (12 male, 7 female) undertook graded exercise (8 min each at ~30%, 40%, 50%, 60%, 70%, and 80% VO2peak) on a cycle ergometer on two occasions separated by either 7 or 14 days. Trials included ingestion of boluses of either (i) plain water (3.8 mL kg body mass-1) (CON) or (ii) ßHB salts (0.38 g kg body mass-1) in plain water (3.8 mL kg body mass-1) (KET), at both 60 min and 15 min prior to exercise. During KET, plasma [ßHB] increased to 0.33 ± 0.16 mM prior to exercise and 0.44 ± 0.15 mM at the end of exercise (both p < .05). Plasma glucose was 0.44 ± 0.27 mM lower (p < .01) 30 min after ingestion of KET and remained ~0.2 mM lower throughout exercise compared to CON (p < .001). Respiratory exchange ratio (RER) was higher during KET compared to CON (p < .001) and 0.03-0.04 higher from 30%VO2peak to 60%VO2peak (all p < .05). No differences in plasma lactate, rate of perceived exertion, or gross or delta efficiency were observed between trials. Gastrointestinal symptoms were reported in 13 out of 19 participants during KET. Acute ingestion of ßHB salts induces nutritional ketosis and alters the metabolic response to exercise in trained cyclists. Elevated RER during KET may be indicative of increased ketone body oxidation during exercise, but at the plasma ßHB concentrations achieved, ingestion of ßHB salts does not affect lactate appearance, perceived exertion, or muscular efficiency.